Pengenalan Sampah Organik dan Anorganik serta Cara Pengolahannya Menjadi Produk Sederhana bagi Siswa SD Negeri Kassi Makassar - Karim, Syahruni; Dwiyanti, Dwiyanti; Sulfaidah, Sulfaidah; Hamran, Hamran (JKM: Jurnal Kemitraan Masyarakat, 2025)
The purpose of this community service is to help students at SD Negeri Kassi Makassar gain knowledge/education about types of waste and learn how to process waste into simple products. Community service activities are carried out at SD Negeri Kassi Makassar. The method in implementing this service is the training method or providing counseling on types of waste and how to process waste simply. The results of the community service activities carried out are that students have an understanding of the types of waste and know how to process waste into simple products. It is hoped that this community service activity will help students improve their skills in creating simple products from waste, especially in helping them become better at innovating.